2009
DOI: 10.1093/dnares/dsp003
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Lager Brewing Yeast, an Interspecies Hybrid

Abstract: This work presents the genome sequencing of the lager brewing yeast (Saccharomyces pastorianus) Weihenstephan 34/70, a strain widely used in lager beer brewing. The 25 Mb genome comprises two nuclear sub-genomes originating from Saccharomyces cerevisiae and Saccharomyces bayanus and one circular mitochondrial genome originating from S. bayanus. Thirty-six different types of chromosomes were found including eight chromosomes with translocations between the two sub-genomes, whose breakpoints are within the ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
408
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(447 citation statements)
references
References 53 publications
22
408
2
7
Order By: Relevance
“…Lager strains are allopolyploid hybrids of Saccharomyces cerevisiae and a Saccharomyces bayanus-like yeast 15,53 that was recently identified as Saccharomyces eubayanus sp. nov. 44 .…”
Section: Flo Genotypes and Phenotypes In Brewer's Yeast Strainsmentioning
confidence: 99%
“…Lager strains are allopolyploid hybrids of Saccharomyces cerevisiae and a Saccharomyces bayanus-like yeast 15,53 that was recently identified as Saccharomyces eubayanus sp. nov. 44 .…”
Section: Flo Genotypes and Phenotypes In Brewer's Yeast Strainsmentioning
confidence: 99%
“…The array-CGH experiments revealed that the SB-type Chromosome XI left arm was missing, and relative hybridization ratios of the SC-type Chromosome X right arm of Weihenstephan34/70-1A was decreased. Nakao et al 9 reported that some bottom fermenting yeast strains possessed a chimera-type Chromosome XI (SC left arm -SB right arm). The reason why signals of the SBtype Chromosome XI left arm of Weihenstephan34/70-1A were missing, seemed to be that SB-type Chromosome XI was missed from the Weihenstephan34/70-1A genome, while chimera-type Chromosome XI (SC left arm -SB right arm) remained.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why signals of the SBtype Chromosome XI left arm of Weihenstephan34/70-1A were missing, seemed to be that SB-type Chromosome XI was missed from the Weihenstephan34/70-1A genome, while chimera-type Chromosome XI (SC left arm -SB right arm) remained. It has been reported that some bottom fermenting yeast strains possess a chimera-type Chromosome Xs (SC left arm -SB right arm, SB left arm -SC right arm) 9,12 . Thus, the reason why the signal of the SC-type Chromosome X right arm of Weihenstephan 34/70-1A was decreased appears to be similar in the case of Chromosome XIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations